Data Protection in Financial Technology Services (A Study in Indonesian Legal Perspective) - Dian Purnama Anugerah; Masitoh Indriani (Sriwijaya Law Review, 2018)
The banking sector is facing a new competitor, namely Financial Technology (Fin-tech). Fin-tech itself can be described as an industry composed of companies using a new tech-nology and innovation with available resources in order to compete in the marketplace of tradi-tional financial institutions and intermediaries in the delivery of financial services. In Indonesia, Fin-tech has been widely developed since the past 3 years. Fin-tech faces a new challenge as a new service for financial consumer which adapts to new ways of living in modern digital tech-nology era. Basically, Fin-tech offers three main categories such as payment, personal finance, and financing. In financing application there are peer to peer financing, social crowd funding, and loan marketplace. All of these kinds of application have some issues in legal framework and data protection due to the use of communication technologies such as internet, social networks, Smartphone, massive use of data with the Big Data, connected objects, etc. The use of big data and those new technologies create new opportunities for these sectors, and this development also raises significant data protection concerns. This paper discusses two legal issues of Fin-tech, the legal aspect, and the data protection.